Exploiting the natural poly(3-hydroxyalkanoates) production capacity of Antarctic Pseudomonas strains: from unique phenotypes to novel biopolymers. (1st August 2019) - Pacheco, Nicolas; Orellana-Saez, Matias; Pepczynska, Marzena; Enrione, Javier; Bassas-Galia, Monica; Borrero-de Acuña, Jose M; Zacconi, Flavia C; Marcoleta, Andrés E; Poblete-Castro, Ignacio
Abstract: Extreme environments are a unique source of microorganisms encoding metabolic capacities that remain largely unexplored. In this work, we isolated two Antarctic bacterial strains able to produce poly(3-hydroxyalkanoates) (PHAs), which were classified after 16S rRNA analysis as Pseudomonas sp. MPC5 and MPC6. The MPC6 strain presented nearly the same specific growth rate whether subjected to a temperature of 4 °C 0.18 (1/h) or 30 °C 0.2 (1/h) on glycerol. Both Pseudomonas strains produced high levels of PHAs and exopolysaccharides from glycerol at 4 °C and 30 °C in batch cultures, an attribute that has not been previously described for bacteria of this genus. The MPC5 strain produced the distinctive medium-chain-length-PHA whereas Pseudomonas sp. MPC6 synthesized a novel polyoxoester composed of poly(3-hydroxybutyrate- co -3-hydroxyhexanoate- co -3-hydroxyoctanoate- co -3-hydroxydecanoate- co -3-hydroxydodecanoate). Batch bioreactor production of PHAs in MPC6 resulted in a titer of 2.6 (g/L) and 1.3 (g/L), accumulating 47.3% and 34.5% of the cell dry mass as PHA, at 30 and 4 °C, respectively. This study paves the way for using Antarctic Pseudomonas strains for biosynthesizing novel PHAs from low-cost substrates such as glycerol and the possibility to carry out the bioconversion process for biopolymer synthesis without the need for temperature control.